Importance and Necessity of Peace Education in the School Curriculum for Fostering International Perspective - Manzoor Bhat, Rashid; Laxmi Jamatia, Purna (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The rise of materialism and militarism was promoted by the industrial revolution. Indirectly, militarism affected the outbreak of war by encouraging the growth of the armaments industry. In order to create the reality of battle, cultural and educational manipulations are used to reinforce group identification and build images of the enemy as well as their possibilities. Denial of human values leads to the death of innocent civilians, especially children and women, as a result of the tendency to dehumanise the enemy. Love, camaraderie, and worldwide understanding are instilled and built via Peace Education. The term "peace education" is not synonymous with "education for peace." In the case of the latter, peace is included in the curriculum. In the first case, peace is used as a guiding principle in the schooling process. Education for peace is not just training for a job; it is education for life. Education for peace aims to teach people the values, skills, and attitudes they need to be wholesome individuals who live in harmony with others and as responsible citizens. Peace education serves as a preventative measure to keep youngsters from becoming entangled in the societal norms that perpetuate violence. It's about learning the skills, attitudes and values that will help you build and maintain peace.